Assessment practices of science process skills in the classroom: an evaluation - Abu Naim, Hamimah (2014)
This study aimed to assess the overall implementation of the practices of Science Process Skills Assessment (SPSA) in the classroom for subjects of science Form 2 in terms of dimensional context, input, process and products and its relationship with student’s level of mastery based on model CIPP. Evaluation on the dimensions of the context is the assessment carried out on its parallels the implementation of SPSA in the classroom with the policies, principles and methods of implementation. Input dimension assessment was conducted on valuation provided input in terms of curriculum content, availability and competency of teachers and infrastructure that help in the implementation of the SPSA. The assessment of the dimensions of the process is the evaluation of the processes and implementation of SPSA by teachers in the classroom. Product dimensions evaluation emphasizes the effectiveness of implementation of SPSA on the level of Science Process Skill (SPS) students. Researchers using qualitative and quantitative affiliate review. Qualitative method used in the evaluation context, input assessment and evaluation process. Interview Protocol and checklist for official documents is an instrument used in qualitative methods. Interviews will be conducted on the study participants consisted of teachers who teach Science subjects Form 2. Quantitative methods were used in the assessment of the inputs, processes and products. Instrument in use is Science Process Skill Test to be administered to the formers.